2010
DOI: 10.1038/icb.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of TLRs by LMW‐HA induces self‐defense mechanisms in vaginal epithelium

Abstract: The innate immune system is present throughout the female reproductive tract and functions in synchrony with the adaptive immune system to provide protection in a way that enhances the chances for fetal survival, while protecting against potential pathogens. Recent data show that activation of Toll-like receptor (TLR)2 and 4 by low-molecular weight hyaluronic acid (LMW-HA) in the epidermis induces secretion of the antimicrobial peptide b-defensin 2. In the present work, we show that LMW-HA induces vaginal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
0
24
1
2
Order By: Relevance
“…Previous studies have shown that incubating vaginal cells in vitro with low molecular weight (LMW) HA (< 200 kDa) elicits an innate immune response characterised by the synthesis of host defence (HD) molecules, including the defensins 1–3 and lactoferrin 31. In contrast, treatment of vaginal VK2 E6/E7 and bladder RT4 cells for 24 h with HMW HA did not affect the expression of either the DEFB4 or LCN2 genes, encoding the host defence agents BD2 and LCN2 (NGAL; Figure 2a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that incubating vaginal cells in vitro with low molecular weight (LMW) HA (< 200 kDa) elicits an innate immune response characterised by the synthesis of host defence (HD) molecules, including the defensins 1–3 and lactoferrin 31. In contrast, treatment of vaginal VK2 E6/E7 and bladder RT4 cells for 24 h with HMW HA did not affect the expression of either the DEFB4 or LCN2 genes, encoding the host defence agents BD2 and LCN2 (NGAL; Figure 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…While the lack of innate responses to the HMW material alone suggested no contamination with LMW material, it cannot be excluded the endogenous production of LMW HA during the challenge period was responsible for the enhanced effector responses. LMW HA has been reported to function through TLRs 2 and 4, but independently of CD44, to stimulate the synthesis of host defence effectors including BD2 and SLPI in vaginal cells 31. Surprisingly, however, in view of its pro‐inflammatory properties,32 these responses observed using the VK2E6/E7 cell model were reported to be independent of pro‐inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 98%
“…TLR4 regulates the expression of human ␤-defensin 2 (H␤D2) in epithelium following stimulation with LPS (48). The same cell surface receptor, TLR4, mediates the induction of H␤D2, without an accompanying increase in inflammatory cytokine production, in human keratinocytes exposed to low molecular weight HA (40) and vaginal epithelium (41). Our group has recently demonstrated the TLR4-dependent induction of murine H␤D2 ortholog in colonic epithelium in vivo following the administration of synthetic, specific sized HA (39).…”
mentioning
confidence: 99%
“…A polydispersed HA fragment preparation of polymers of less than 750 kDa injected intraperitoneally protects wild-type mice in a TLR4-dependent manner from a microflora-mediated epithelial damage model of colitis (37) or from the epithelium-depleting effects of radiation (38). Low molecular weight HA has been also been shown to induce elevated expression of antimicrobial defensin proteins that may contribute to enhanced epithelial defense in the intestine (39), skin (40), and vagina (41).…”
mentioning
confidence: 99%
“…The epithelial barrier integrity plays a critical role in the maintenance of the homeostasis in the vaginal mucosa [2]. Disruption of the epithelial barrier integrity is associated with the pathogenesis of a large number of mucosal diseases, including allergic airway diseases (such as allergic rhinitis, asthma) [3], chronic intestinal inflammation (such as inflammatory bowel disease) [4], and chronic urogenital inflammation (such as chronic vaginitis) [5]. Yet, the causative factors inducing the epithelial barrier disruption are not fully understood.…”
Section: Introductionmentioning
confidence: 99%